"An Investigation on the Correlation between DMFT and OHI- S Indices on 12- Year- Old School Girls in Kashan " - Afshar H; Ershadi A; Ershadi M (Tehran University of Medical Sciences, 2004)
Statement of Problem: DMFT and OHI- S indices are two of the most important quantitative factors, measuring tooth health and oral hygiene, respectively. Propose: The aim of this study was to study of correlation between these indices in 12- year old school girls of Kashan. Materials and Methods: A cross sectional study on the correlation between these indices were carried out on 242, twelve year- old school girls in Kashan and the results, have been presented in this paper. Results: The findings were as follows: Average and standard deviation of decayed, missed and filled teeth were (1.12, 1.5), (0.05, 0.25) and (0.28, 0.92), respectively. Average and standard deviation of DMFT was 1.45 and 1.73, respectively, with 45.5 percent of the cases being caries free (DMFT= O). OHI- S index, on the other hand, showed an average of 1.46 with a standard deviation of 0.42. Conclusion: The result of the 2.test, carried out on the measured data, showed no correlation between the DMFT and OHI-S indices.